Aspectos técnicos, econômicos e ambientais de fazendas de cultivo de camarão marinho nos estuários dos rios Jaguaribe, Coreaú e Acaraú, Ceará, Brasil - Rocha, Ítalo Régis Castelo Branco (2017)
Brazil is the third largest producer of white shrimp, Penaeus vannamei, grown in Latin America. In the country, white shrimp production started during the 1980s, stimulated in response to the international market demand for shrimp of high commercial value. The State of Ceará is in first place in the ranking of production and productive efficiency. Despite the economic importance of farmed shrimp, a number of technical, environmental, economic and social problems have been widely reported in the international literature. Thus, to analyze the technical, environmental and socio-economic impacts related to shrimp farming in the semi-intensive and intensive systems in the State of Ceará, and to identify alternatives for sustainable production, a study was carried out in the estuarine areas of the Jaguaribe, Acaraú and Coreaú that represent the three main production areas of the State of Ceará. The methodology was divided into four main actions: 1) Characterization of the productive processes of the shrimp farms, being the methodology based on field observations, interviews, secondary data analysis, external sources, including official documents and academic literature; 2) Characterization of the benefits and problems of marine shrimpfarm with the methodology based on gathering information about the benefits and problems of this industry. Negative aspects include technical, environmental, economic and social problems; 3) Satellite image processing with the methodology based on the identification and location of the marine shrimp farms using satellite images with a resolution of 15 m per pixel (Landsat Geocover 1999-2000, Landsat 8) Detailed thematic maps were then prepared using digital image interpretation techniques using SPRING 4.2 and ArcGIS 9.0 software. 4) Analysis of water samples, being the methodology based on the interpretation of reports of water collection in marine shrimp farms, carried out in the period 2010-2012. Thus, this study may contribute to the dissemination of good management practices, the development of public policies and the demystification of the main criticisms attributed to Brazilian shrimp farming, facilitating their development in a sustainable way.